If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3a + -2) + -2(r + 1) = 0 Reorder the terms: -4(-2 + 3a) + -2(r + 1) = 0 (-2 * -4 + 3a * -4) + -2(r + 1) = 0 (8 + -12a) + -2(r + 1) = 0 Reorder the terms: 8 + -12a + -2(1 + r) = 0 8 + -12a + (1 * -2 + r * -2) = 0 8 + -12a + (-2 + -2r) = 0 Reorder the terms: 8 + -2 + -12a + -2r = 0 Combine like terms: 8 + -2 = 6 6 + -12a + -2r = 0 Solving 6 + -12a + -2r = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -12a + -6 + -2r = 0 + -6 Reorder the terms: 6 + -6 + -12a + -2r = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -12a + -2r = 0 + -6 -12a + -2r = 0 + -6 Combine like terms: 0 + -6 = -6 -12a + -2r = -6 Add '2r' to each side of the equation. -12a + -2r + 2r = -6 + 2r Combine like terms: -2r + 2r = 0 -12a + 0 = -6 + 2r -12a = -6 + 2r Divide each side by '-12'. a = 0.5 + -0.1666666667r Simplifying a = 0.5 + -0.1666666667r
| 786=x+34+4x-40 | | X/18=-17 | | 8-5x+11+2x+4x-2=22 | | 6(t-5)+6t=4(3t+4)-11 | | 3.5(x+1.4y)+4(1.4x+1.3y)= | | 5+3s-2=8s+3-4s | | (3x+19/5)+(x+47/6)=17 | | (2/17)x=10 | | 3x-3.5=6.4x-16.42 | | 2t+7t=45 | | 7.79=2(3.14*r) | | (8-5i)(8-5i)= | | -(5y+5)-(-4y-6)=-3 | | 7.3x-8=6.3x+1 | | y/20=-26 | | 3(2x-1)+5=13 | | a=1/2(18*24) | | 1/6x=39 | | 17-3x=2x-2 | | 786=x+34+4(x-40) | | 8x5/9 | | -4(2b+3)+(9b-7)=0 | | 5(4x-6)-19x=7 | | 4x+1=2(x-7) | | b+8b-22=0 | | 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 |